Features of expression of immunohistochemical markers in local and generalized clear cell kidney cancer - E. M. Frantsiyants; A. N. Shevchenko; E. A. Dzhenkova; N. S. Karnaukhov; T. A. Gudtskova; A. A. Breus; E. V. Filatova; D. A. Shvyrev (Исследования и практика в медицине)
Purpose of the study. To conduct a comparative analysis of the expression of the following markers: Ki‑67, cyclin D1, E‑cadherin, CD44, MMP‑9, VEGF, P53, vimentin in renal tumor tissue in clear cell kidney cancer depending on the prevalence of the tumor process.Materials and methods. The material for the study was the operating material of 100 patients with light cell kidney cancer who were treated at the National Medical Reseaгch Centгe fог Oncology of the Russian Federation Health Ministry from 2015 to 2018. 50 patients were diagnosed with local cancer (T1–3an0m0), 50 – generalized cancer (T1–4N0M1). For the immunohistochemical (IHC) study, the material was fixed in 10% neutral formalin for 24 hours and encased in paraffin. Dewaxing and restoration of antigenic activity of the material was carried out in the RT module (Thermo Fisher Scientific) using Tris buffer pH=9, for 20 minutes at 98 °C. the Formulation of the IGC reaction was carried out in the immunohistostainer «Autostainer 480S» (Thermo Fisher Scientific). Used system detection UltraVision Quanto Detection System (Thermo Fisher Scientific), and the Chromogen DAB. Antibodies used: E‑cadherin (EP700Y) Cell Marque, 1: 100; CD 44 (EPR1013Y) Cell Marque 1:150; Ki‑67 (SP6) Spring Bio, 1:200; P53 (DO‑7) Cell Marque, 1:200; cyclin D1 (EP12) Dako, 1:200; VEGF Termo Fisher, 1:100; Vimentin (V9) Dako, 1:150; MMP‑9 (EP100902) Epitomics, 1:100. The results of the reactions with markers were evaluated by counting the number of colored cells in each 3rd field of view of the entire drug at magnification of the X200 lens in the AXIO Scope microscope. A1 (Carl Zeiss). The results were expressed as a percentage-the proportion of stained cells in relation to all tumor cells in the field of vision. Parametric methods of statistics were used for statistical processing of the results. The reliability of the difference between the two averages was determined by the student's t‑test for unrelated populations.Results. In clear cell kidney cancer, a low level of proliferative activity was observed in General, but in generalized, compared with local, it was significantly higher (P<0.05) (8±0.5% and 5±0.6%, respectively), and in generalized cancer, there was an overexpression of Cyclin D1–70±3.9%, compared to 14.4±2.3% in local stages, P<0.05. In generalized kidney cancer, epithelial-mesenchymal transformation processes are more pronounced in comparison with local cancer (a significant increase in Vimentin expression by 28% and CD44 by 16.6% (P<0.05), a decrease in E‑cadherin expression by 24% (P<0.05), and activation of neoangiogenesis processes (a significant increase in VEGF expression by 32%, P<0.05). The P53 protein was absent in local kidney cancer cells and was extremely low when generalized – 3.8±0.7%. One of the main markers of extracellular matrix degradation MMP‑9 was approximately at the same level at both stages: at local‑50±6% and 49.6±7.2% at generalized, the difference in indicators is not reliable (P<0.05).Conclusion. Progression of clear cell kidney cancer from local to generalized forms is accompanied by hyperexpression of cyclin D1, a decreased e‑cadherin expression while increasing vimentin expression (increasing signs of epithelial-mesenchymal transformation), an increase in CD44 and VEGF expression.